Penerapan Support Vector Machine Untuk Jalur Peminatan Program Studi - Dion Krisnadi; Nadya D. Bachtiar; Samuel Lukas; Pujianto Yugopuspito; Petrus Widjaja (Prosiding SISFOTEK, 2020)
It is common that in a curriculum of field of study provides some electives subjects to be selected by their students. Some electives subjects are grouped into a major study. Universitas Pelita Harapan Informatics department offers three major studies. They are Software Engineering, Medical Informatics and Intelligent & Interactive Media. These majors are provided in order to fit interest of the students. Students must choose one major for persuing their degree after they finished the first two years studies. This paper discusses on how to implement the Support Vector machines technology for helping students in determining their major based on their academic records. The inputs of the system ere grades of the subjects of the first two years studied and the outputs is the GPA of the electives subjects for each major.